(untitled) (Research, Society and Development, 2021)
Objective: The objective of this work is to report the experience of a university extension project in carrying out health education workshops in the waiting room of a UBS in the interior of Piauí. Method: This is a descriptive study of the experience report type, carried out from January to December 2017 at the Hilda Veras Basic Health Unit, located in the city of José de Freitas PI. The project was supported by the State University of Piauí (UESPI) and the Regional Council of Physiotherapy. The project was composed of academics from the health area and the meetings took place every fortnight, lasting 1 hour per meeting, the choice of this unit was justified by the easy access for the academics. Results: 22 meetings were held at UBS. An important point to be highlighted were the possibilities produced by the welcoming strategies that provided a very close relationship between users, their families and the teams during the practices. We found that the host, with time, was becoming something spontaneous and not plastered or shy, as it was in the first moments. This was evidenced by the fact that some people in the community already started to recognize the project’s students, and thus, look for them for information, help and even a conversation, in order to know their role in the place, which was quite a lot. interesting. Conclusion: Based on the experiences in the extension project, it was possible to promote reflections on the importance of welcoming in Basic Health Units, as well as on the importance of Health Education. In addition to enriching experiences of knowledge exchange with the groups, it was also possible learn more about the active and welcoming methodologies that public policies advocate.